PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 003 PELINTUNG KECAMATAN MEDANG KAMPAI KOTA DUMAI - Arfizal '; Hendri Marhadi Hendri Marhadi; Gustimal witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This research is motivated by low yields social studies fourth grade students of SDN 003 Pelintung Kecamatan Medang Kampai Dumai. For that teachers use berfariatif learning model that can improve learning outcomes. The problem of this research is the application of the model Is STAD cooperative learning can improve learning outcomes IPS 003 fourth grade students of SDN Pelintung Kecamatan Medang Kampai Dumai?. This study aims to improve the results of the fourth grade social studies SDN 003 Pelintung Kecamatan Medang Kampai Dumai with the application of STAD cooperative learning model to material technology development. The design of this study is action research (CAR) conducted as many as two cycles, each cycle consisting of two meetings and one-time daily tests. Obtained from this study of student learning outcomes. Student learning outcomes data after learning using STAD cooperative learning model based on the base score is 58.5% increase in the first cycle an average of 69.0% sufficient category and the second cycle an average of 82.0% is very good. While the activities of teachers also increased from 58.35% to 91.65% less of a category of either category once and student activity 83.74% to 94.59% category either be very good category. From this study it can be concluded that the application of Cooperative Learning Model of type Student Team Achievement Division (STAD) can improve learning outcomes IPS 003 fourth grade students of SDN Pelintung Kecamatan Medang Kampai Dumai. Keywords: Student Team Achievement Division (STAD), IPS Learning Outcomes.